PENGEMBANGAN KEMAMPUAN BERPIKIR GENERIK MAHASISWA CALON GURU MELALUI PEMBELAJARAN FISIKA MODERN - Hartono, -; Subali, Bambang (Lembaran Ilmu Kependidikan, 2010)
This research develops the ability in generic thinking to the future physics teachersthrough modern physics learning such as: understanding in sense of scale andsymbolic languages, doing inference, comprehending causality, and doingmathematics modeling. The subject of the research was teacher students who tookmodern physics in third semester. They were encouraged to be actively involved in thelearning process individually in the classroom and was assigned indepedent tasksoutside the class by relying on the resources on the Internet. The result of the researchshowed a significant improvement on five generic capabilities for high GPA groupand four generic capabilities for low GPA group. The only one skill that did notimprove is capability in doing mathematics modeling for low GPA group. It issuggested that there is an expansion of the implementation of physics learning whichis oriented towards the development of generic thinking, including its subskills.Kata kunci: berpikir generik, fisika modern, mahasiswa calon guru